A new evaluation method of dented natural gas pipeline based on ductile damage. (June 2023) - Wu, Ying; Du, Zhuohong; Li, Linya; Tian, Zhongxu
Highlights: Defined pipeline monitoring threshold and pipeline repairing threshold. Investigated the effects of indenter and pressure on the pipeline thresholds. Proposed a dent evaluation method based on pipeline threshold. Abstract: Dent is the most common defect on natural gas pipelines, leading to pipe leakage or rupture. Since the dent depth-based failure criterion is unreasonable, this work proposed a new ductile damage-based evaluation method for dented natural gas pipelines. The new method was proposed by finite element analysis combined with Oyane ductile damage criterion. Specifically, a finite element-based model was developed to model the formation process of an unconstrained dent, and its accuracy was verified by comparison with test data. A new parameter called the pipeline defect parameter was defined as the ratio of the dent depth to the pipeline diameter to illustrate the dimensionless of dent depth. Then, two safety indicators based on pipeline defect parameter, i.e., monitoring and repairing thresholds, of dented pipelines were determined considering the dent springback. The parameter effects, i.e., indenter geometries and size, as well as internal pressure, were determined. Finally, the proposed method's adaptability and reasonable were demonstrated by case studies. It is expected to provide a useful method for operating dented natural gas pipelines safely.